Information-seeking behavior of U.P. Diliman History major students towards archives - Eclevia, Carlos Jr. L.; Rey, Emma M. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2006)
This study focused on the information-seeking behavior of selected students of the Department of History, University of the Philippines Diliman. Basically, it sought answers to achieve the following objectives:(1) to analyze how the UP History Major students use the archives in the course of their research; (2) to know the ways on searching the information they need in the archives; (3) to determine the means for searching primary materials or sources that they think are helpful; and (4) to find out the usual problems they encounter when doing their research. The respondents were ten graduate and four Ph.D. students, who were conducting research during the semester that this study was done. To gather substantial data, survey questionnaires were used as the primary research instrument, and informal interviews with the respondents and some History professors were also conducted.
Using the six-stage model of information behavior developed by Kuhlthau and Ellis, the findings of this study revealed that the students became more confident with their ideas after discussing them with their teachers, archivists, librarians and peers. Familiarization with the system and existing archival services also decrease their uncertainty and anxiousness in using the archives for their research. The students also browsed materials in the library and read notes to supplement their research. Some just preferred to select a topic that was related to a paper they had written in the past, which was usually based on their personal interest. Preliminary searching had also been considered an important action by the students to set focus and then started to look for other relevant sources, both print and non-print. They had different ways in seeking and locating the information they needed. They located their needed primary materials by means of traditional, electronic, remote and other repository retrieval strategies. They also conducted interviews and borrowed materials from professors, colleagues and collectors. Finally, most of the respondents were satisfied with the outcome of their research.
As seen in the results, the students started with merely having vague ideas and ended up with the much clearer and focused topic. The information-seeking behavior of the History students was non-linear and dependent on factors such as topic, availability of materials, teacher's suggestions, services available in the archives and libraries, and time.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines, Diliman -- Students; Information services -- Philippines -- Quezon City -- User Studies; History students -- Philippines -- Quezon City; Archives -- Reference services -- Philippines -- Quezon City